Effects of family-centered care on bonding: A systematic review - Kutahyalioglu, Nesibe S; Scafide, Katherine N (SAGE Publications, 2022)
Most critically ill neonates require constant monitoring, continuous care, and supervision. However, distance created by admission and prolonged stay in a neonatal intensive care unit (NICU) may contribute to a delay in parent-infant bonding. This review aimed to determine how family-centered care (FCC) in the NICU affects parental bonding with critically ill infants. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used to perform a systematic search of the literature within the following four electronic databases: Cumulative Index of Nursing and Allied Health Literature (CINAHL), MEDLINE, Cochrane Library, and Web of Science. The search was conducted through July/August 2020. Research quality was evaluated using the Johns Hopkins Nursing Evidence-Based Practice Grading Scale. Out of 816 articles identified through literature search, 16 of the studies met our inclusion criteria. The majority of the studies ( n = 14) found FCC interventions resulted in a significant increase in parental bonding. Results showed evidence practicing FCC in the NICU setting supports early parent-infant bonding. Nurses should consider implementing evidence-based FCC strategies into practice, such as allowing parents unrestricted access to their infants. More rigorous research with larger samples is recommended. More studies are also needed focusing on father-infant dyads and mother-father-infant triads.
Keywords: Hospitalization; Parents; Critical Illness; Intensive Care Units, Neonatal; Patient-Centered Care; Infant, Newborn; Infant; Humans; 3. Good health